2022
DOI: 10.1161/jaha.121.021720
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent Impact of Sex on the Long‐Term Outcomes After Left Main Revascularization

Abstract: Background There are still limited data about the differential effect of sex on long‐term outcomes after percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) for left main coronary artery disease. This extended follow‐up study of the MAIN‐COMPARE (Ten‐Year Outcomes of Stents Versus Coronary‐Artery Bypass Grafting for Left Main Coronary Artery Disease) registry evaluated clinical outcomes beyond 10 years. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…20 The extended follow-up of the MAIN-COMPARE (Ten-Year Outcomes of Stents Versus Coronary-Artery Bypass Grafting for left Main Coronary-Artery Bypass Grafting for Left Main Coronary Artery Disease) trail also revealed lower all-cause mortality and serious composite outcomes at 10 years in female compared with male, and this difference was mainly driven by the higher event rate in male during the late period between 5 and 10 years. 21 On the contrary, multiple lines of evidence have documented the poorer prognosis of female compared to male due to various pathologic resultant such as medical co-morbid conditions, coronary microvascular dysfunction and diastolic filling pattern. 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…20 The extended follow-up of the MAIN-COMPARE (Ten-Year Outcomes of Stents Versus Coronary-Artery Bypass Grafting for left Main Coronary-Artery Bypass Grafting for Left Main Coronary Artery Disease) trail also revealed lower all-cause mortality and serious composite outcomes at 10 years in female compared with male, and this difference was mainly driven by the higher event rate in male during the late period between 5 and 10 years. 21 On the contrary, multiple lines of evidence have documented the poorer prognosis of female compared to male due to various pathologic resultant such as medical co-morbid conditions, coronary microvascular dysfunction and diastolic filling pattern. 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…18 The MAIN-COMPARE Registry showed that at 10 years women had a lower incidence of death and serious adverse outcomes than men, with the risks of adverse outcomes varying by revascularization technique over time. 19 In the short term (up to 1 year), compared with CABG, PCI had a lower risk for composite serious outcomes, namely death, MI, stroke, or repeat revascularization (aHR 0.41; 95% CI [0.19-0.91]; p=0.03). From 1 to 5 years, PCI had a higher risk for death (aHR 33.99; 95% CI [2.01-7.92]; p<0.001) and composite outcomes (aHR 2.93; 95% CI [1.59-5.39]; p=0.001).…”
Section: Registry Datamentioning
confidence: 98%
“…The 5-to 10-year risks were similar for PCI and CABG in women. 19 Overall, the optimal revascularization modality for women with LMS CAD remains undetermined. Women appear to have a trend towards worse outcomes with PCI than CABG, but all trials have enrolled relatively small numbers of female patients.…”
Section: Registry Datamentioning
confidence: 99%
“…In this issue of the Journal of the American Heart Association (JAHA) , Yoon et al address the important question of long‐term outcomes in women undergoing PCI versus CABG for LMCAD. 17 This extended follow‐up of the MAIN‐COMPARE registry (Revascularization for Unprotected Left Main Coronary Artery Stenosis: Comparison of Percutaneous Coronary Angioplasty Versus Surgical Revascularization from Multi‐Center Registry) included consecutive patients who underwent PCI or CABG for LMCAD in South Korea from January 2000 to June 2006 with either bare metal stents or first‐generation DES (the devices available at the time of treatment). To compensate for the nonrandomized design of the study, the authors used inverse‐probability‐treatment weighting for the primary analysis.…”
mentioning
confidence: 99%